THE ROLE OF MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Behruzkhon Yuldoshev Behzod ugli (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article examines the importance of motivation in learning English as a foreign language (EFL). Motivation is one of the most influential factors affecting learners’ success in language acquisition. The paper discusses different types of motivation—intrinsic and extrinsic—and how they influence learners’ attitudes, performance, and achievement in English. It also highlights the role of teachers in fostering and maintaining students’ motivation through effective teaching methods, feedback, and classroom environment.